Genetic variation of Glucose Transporter-1 (GLUT1) and albuminuria in 10,278 European Americans and African Americans: a case-control study in the Atherosclerosis Risk in Communities (ARIC) Study - Heilig Charles W; Brancati Frederick L; Gambir Tejal; Steffes Michael W; Kao Wenhong L; Hsu Charles C; Shuldiner Alan R; Boerwinkle Eric A; Coresh Josef (BMC, 2011)
Abstract Background Evidence suggests glucose transporter-1(GLUT1) genetic variation affects diabetic nephropathy and albuminuria. Our aim was to evaluate associations with albuminuria of six GLUT1 single nucleotide polymorphisms(SNPs), particularly XbaI and the previously associated Enhancer-2(Enh2) SNP. Methods A two-stage case-control study was nested in a prospective cohort study of 2156 African Americans and 8122 European Americans with urinary albumin-to-creatinine ratio(ACR). Cases comprised albuminuria(N = 825; ≥ 30 μg/mg) and macroalbuminuria(N = 173; ≥ 300 μg/mg). ACR < 30 μg/mg classified controls(n = 9453). Logistic regression and odds ratios(OR) assessed associations. The evaluation phase(stage 1, n = 2938) tested associations of albuminuria(n = 305) with six GLUT1 SNPs: rs841839, rs3768043, rs2297977, Enh2(rs841847) XbaI(rs841853), and rs841858. Enh2 was examined separately in the replication phase(stage 2, n = 7340) and the total combined sample (n = 10,278), with all analyses stratified by race and type 2 diabetes. Results In European Americans, after adjusting for diabetes and other GLUT1 SNPs in stage 1, Enh2 risk genotype(TT) was more common in albuminuric cases(OR = 3.37, P = 0.090) whereas XbaI (OR = 0.94, p = 0.931) and remaining SNPs were not. In stage 1, the Enh2 association with albuminuria was significant among diabetic European Americans(OR = 2.36, P = 0.025). In African Americans, Enh2 homozygosity was rare(0.3%); XbaI was common(18.0% AA) and not associated with albuminuria. In stage 2(n = 7,340), Enh2 risk genotype had increased but non-significant OR among diabetic European Americans(OR = 1.66, P = 0.192) and not non-diabetics(OR = 0.99, p = 0.953), not replicating stage 1. Combining stages 1 and 2, Enh2 was associated with albuminuria(OR 2.14 [1.20-3.80], P = 0.009) and macroalbuminuria(OR 2.69, [1.02-7.09], P = 0.045) in diabetic European Americans. The Enh2 association with macroalbuminuria among non-diabetic European Americans with fasting insulin(OR = 1.84, P = 0.210) was stronger at the highest insulin quartile(OR = 4.08, P = 0.040). Conclusions As demonstrated with type 1 diabetic nephropathy, the GLUT1 Enh2 risk genotype, instead of XbaI, may be associated with type 2 diabetic albuminuria among European Americans, though an association is not conclusive. The association among diabetic European Americans found in stage 1 was not replicated in stage 2; however, this risk association was evident after combining all diabetic European Americans from both stages. Additionally, our results suggest this association may extend to non-diabetics with high insulin concentrations. Rarity of the Enh2 risk genotype among African Americans precludes any definitive conclusions, although data suggest a risk-enhancing role.